Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To determine \(\vec{c}\) in the equation \(3 \vec{a} + 2 \vec{b} - \vec{c} = 0\), we can follow these steps:
1. Express the vectors \(\vec{a}\) and \(\vec{b}\) in component form:
[tex]\[ \vec{a} = -2 \hat{i} + \hat{j} - 3 \hat{k} \][/tex]
[tex]\[ \vec{b} = 5 \hat{i} + 3 \hat{j} - 2 \hat{k} \][/tex]
2. Multiply \(\vec{a}\) by 3 and \(\vec{b}\) by 2:
[tex]\[ 3 \vec{a} = 3(-2 \hat{i} + \hat{j} - 3 \hat{k}) = -6 \hat{i} + 3 \hat{j} - 9 \hat{k} \][/tex]
[tex]\[ 2 \vec{b} = 2(5 \hat{i} + 3 \hat{j} - 2 \hat{k}) = 10 \hat{i} + 6 \hat{j} - 4 \hat{k} \][/tex]
3. Add the scaled vectors \(3 \vec{a}\) and \(2 \vec{b}\):
[tex]\[ 3 \vec{a} + 2 \vec{b} = (-6 \hat{i} + 3 \hat{j} - 9 \hat{k}) + (10 \hat{i} + 6 \hat{j} - 4 \hat{k}) \][/tex]
[tex]\[ 3 \vec{a} + 2 \vec{b} = (-6 + 10) \hat{i} + (3 + 6) \hat{j} + (-9 - 4) \hat{k} \][/tex]
[tex]\[ 3 \vec{a} + 2 \vec{b} = 4 \hat{i} + 9 \hat{j} - 13 \hat{k} \][/tex]
4. Rearrange the original equation and solve for \(\vec{c}\):
[tex]\[ 3 \vec{a} + 2 \vec{b} - \vec{c} = 0 \][/tex]
[tex]\[ \vec{c} = 3 \vec{a} + 2 \vec{b} \][/tex]
Substituting the result from step 3:
[tex]\[ \vec{c} = 4 \hat{i} + 9 \hat{j} - 13 \hat{k} \][/tex]
Therefore, the correct value for \(\vec{c}\) is:
1) \(4 \hat{i} + 9 \hat{j} - 13 \hat{k}\).
The answer is choice (1).
1. Express the vectors \(\vec{a}\) and \(\vec{b}\) in component form:
[tex]\[ \vec{a} = -2 \hat{i} + \hat{j} - 3 \hat{k} \][/tex]
[tex]\[ \vec{b} = 5 \hat{i} + 3 \hat{j} - 2 \hat{k} \][/tex]
2. Multiply \(\vec{a}\) by 3 and \(\vec{b}\) by 2:
[tex]\[ 3 \vec{a} = 3(-2 \hat{i} + \hat{j} - 3 \hat{k}) = -6 \hat{i} + 3 \hat{j} - 9 \hat{k} \][/tex]
[tex]\[ 2 \vec{b} = 2(5 \hat{i} + 3 \hat{j} - 2 \hat{k}) = 10 \hat{i} + 6 \hat{j} - 4 \hat{k} \][/tex]
3. Add the scaled vectors \(3 \vec{a}\) and \(2 \vec{b}\):
[tex]\[ 3 \vec{a} + 2 \vec{b} = (-6 \hat{i} + 3 \hat{j} - 9 \hat{k}) + (10 \hat{i} + 6 \hat{j} - 4 \hat{k}) \][/tex]
[tex]\[ 3 \vec{a} + 2 \vec{b} = (-6 + 10) \hat{i} + (3 + 6) \hat{j} + (-9 - 4) \hat{k} \][/tex]
[tex]\[ 3 \vec{a} + 2 \vec{b} = 4 \hat{i} + 9 \hat{j} - 13 \hat{k} \][/tex]
4. Rearrange the original equation and solve for \(\vec{c}\):
[tex]\[ 3 \vec{a} + 2 \vec{b} - \vec{c} = 0 \][/tex]
[tex]\[ \vec{c} = 3 \vec{a} + 2 \vec{b} \][/tex]
Substituting the result from step 3:
[tex]\[ \vec{c} = 4 \hat{i} + 9 \hat{j} - 13 \hat{k} \][/tex]
Therefore, the correct value for \(\vec{c}\) is:
1) \(4 \hat{i} + 9 \hat{j} - 13 \hat{k}\).
The answer is choice (1).
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.